Historiographic Mapping of Knowledge Domains Literature - Garfield, Eugene (Journal of information science, 2004)
To better understand the topic of this colloquium, we have created a series of databases related to knowledge domains (dynamic systems [small world/Milgram], information visualization [Tufte], co-citation [Small], bibliographic coupling [Kessler], and scientometrics [Scientometrics]). I have used a software package called HistCiteTM which generates chronological maps of subject (topical) collections resulting from searches of the ISI Web of Science1 or ISI citation indexes (SCI, SSCI, and/or AHCI) on CD-ROM. When a marked list is created on WoS, an export file is created which contains all cited references for each source document captured. These bibliographic collections, saved as ASCII files, are processed by HistCite in order to generate chronological and other tables as well as historiographs which highlight the most-cited works in and outside the collection. HistCite also includes a module for detecting and editing errors or variations in cited references as well as a vocabulary analyzer which generates both ranked word lists and word pairs used in the collection. Ideally the system will be used to help the searcher quickly identify the most significant work on a topic and trace its year-by-year historical development. In addition to the collections mentioned above, historiographs based on collections of papers that cite the Watson-Crick 1953 classic paper identifying the helical structure of DNA were created. Both year-by-year as well as month-by-month displays of papers from 1953 to 1958 were necessary to highlight the publication activity of those years.